Unlocking SME finance in Asia roles of credit rating and credit guarantee schemes - Yoshino, Naoyuki 1950-; Taghizadeh-Hesary, Farhad (Routledge studies in development economics, 2020)
There is limited access for small and medium-sized enterprises (SMEs) to bank credit. This book proposes new and sustainable models to help ease the access of SMEs to finance and boost economic growth and job creation in Asia. This book looks at the difficulties of SMEs in accessing finance and suggests ways on how to mitigate these challenges. It suggests how we can develop credit information infrastructures for SMEs to remedy the asymmetric information problem and to utilize credit rating techniques for the development of a sustainable credit guarantee scheme. The book provides illustrations of various Asian economies that implemented credit guarantee schemes and credit risk databases and is a useful reference for lessons and policy recommendations